(untitled) (Al-Academy, 2023)
Art is a language in which the artist expresses himself, his society, and the events he lives in, so new artistic trends emerged, so the artist no longer practices his art as required by any previous artistic rules. And the thoughts wandering inside him, which led him to the abstract method in which the artist tries to employ the elements of the artwork in a plastic construction through which he achieves the relationships of the abstract form through the rhythms of lines, colors, spaces, shapes and textures without these plastic elements having any connection with the visual reality.The research aims to find a new vision inspired by the school of geometric abstraction to enrich the field of Saudi plastic painting. And to take advantage of the characteristics of the school of geometric abstraction to produce innovative paintings in the field of plastic painting. The research dealt with the geometric abstract school in terms of the concept, its origin, and its most important artists and works. The research community consisted of the total artistic productions carried out by the artist, as an intentional sample of artists who dealt with the geometric abstract school style was chosen in their artistic production. The researcher followed the analytical descriptive approach in tracking the literature related to the geometric abstract school, and the experimental approach in conducting the research experiment. The researcher reached the following results: 1- Introducing new visions from the geometric abstraction school with various techniques with distinctive rhythmic systems produced by the artist’s thought and imagination through the geometric abstraction school method, which affected the flat plastic painting.2- Geometric abstraction is characterized by strong tools and elements such as: fragmentation, simplification, compositions, overlapping lines and colors, in addition to methods of repetition, vertical and horizontal perpendiculars, and oblique axes in a structural relationship.3- The artist was able to reflect his emotions on the lines, colors and tools he used to produce the artwork according to what he deems appropriate in the style of the geometric abstract school.